Characterization of ginger rhizome lectin and its efficacy in controlling red spider mite in tea - Sathyapriya, P.; Kalaivani, A.; Arvinth, S.; Roobakkumar, A.; Kumar, R. Raj; Kumar, P. Mohan (Journal of Plantation Crops, 2013)
Methodology was developed to isolate and characterize the ginger rhizome lectin and its applied aspects in integrated pest management in tea. Lectin, a defense protein with mannose specificity was purified from fresh rhizomes of ginger (Zingiber officinale Roscoe) by affinity chromatography. Purified fractions of lectin showed agglutination with rabbit erythrocytes. SDS PAGE analysis revealed the presence of 15 KDa ginger rhizome lectin. Bio-efficacy of purified ginger rhizome lectin was experimented on red spider mite (Oligonychus coffeae Nietner) under in-vitro conditions. It was observed that 100 µg ml–1 of purified lectin caused in toto mortality of adult red spider mite. Identical results were observed in terms of ovipositional deterrence of red spider mite at 100 µg ml–1 of ginger rhizome lectin. Results suggest that ginger rhizome could be used as an alternative plant source for lectin isolation and it can be used as an acaricide in the IPM schedule or organic tea fields.